Pengaruh Beban Kerja dan Sistem Penghargaan Terhadap Kinerja Pegawai - Benny Benyamin Situmorang; Indah Rizki Maulia; Cayla Salsa Raya; Vira Anggita Sukma (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The article "Work Load Impact and Reward System" is an academic writing that provides reading material. The purpose of writing this article is to explain the effect of labour restrictions and reward systems on a worker's work. In addition, in the field of Human Resource Management, it is necessary to come up with a hypothesis about the effect or direction of the variable on the main objective of the research concerned. The methods used to write articles are primary research methodologies, which come from online sources such as Google Scholar, Mendeley, and other online academic sources. Using k-means analysis The results of this article are: 1) ; Workload has a significant effect on employee performance 2); The reward system has a significant effect on employee performance 3) ; Workload and reward systems have a significant effect on employee performance.